Impact of Parent Education and Transformative Leadership Role on Children’s Academic Performance - Chandio, Abdul Rahim; Ali, Manzoor (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2024)
This study is concerned to explore the impacts of a parental education andtransformative leadership role on children’s academic performance. Afterdelivering a brief literature review, study support the significance andimplications of an educated family, availability of modern facilities, andtransformative leadership role to become a productive to meet the educationalgoals and it also impacts the educational policies and education professionals.Numerous research items assist to measure the impacts of parents’ education,modern accessible modern facilities, and motivating and visional leadershipon children’s academic outcome and development. In this study Selfadministered questionnaires were designed and random sampling wascollected from three public Degree colleges in Sindh, Pakistan. The dataanalysis was carried out by means of descriptive and inferential statistics inwhich Kendall’s tau C tests and Kruskal- Wallis H-test were used to meet thehypotheses tests. The findings of the study support the positive association ofparent education, convenience of modern facilities, and motivating andvisional role on their children’s academic performance. In demographiccharacteristics respondents’ different background was encircled and a broadinfluence of parent education and leadership on children academicperformance was supported in a wide literature